Applying GIS tools for analysing urban thermal environment - De Souza, Léa Cristina Lucas [UNESP] (2006)
A methodology for analyzing the solar access and its influence on both air temperature and thermal comfort of the urban environment was here developed by applying the potentiality of GIS tools. Urban canyons in a specific area of a Brazilian medium sized city were studied. First, a computational algorithm was applied in order to allow the determination of sky view factors (SVF) and sun-paths in urban canyons. Then, air temperatures in 40 measurement points were collected within the study area. Solar radiation values of these canyons were determined and subsequently stored in a GIS database. The creation of thermal maps for the whole neighbourhood was possible due to a statistical treatment of the data, by promoting the interpolation of values. All data could then be spatially cross-examined. In addition, thermal comfort maps for summer and winter periods were generated. The methodology allowed the identification of thermal tendencies within the neighbourhood, what can be useful in the conception of guidelines for urban planning purposes.